Role of Coaching in the Hungarian Economic Development – With Particular Attention to Management Development and Internal Audit - Kunos, István (Public Finance Quarterly, 2022)
With its well-developed methodology and potentials adjusted to the social requirements of the present time, coaching may give efficient support - to individuals, groups and even wider circles - for solving problems in nearly every area of life while carrying several ‘additional’ benefits. An appropriately completed coaching process always results in the deepening of self-knowledge, which is the key element of the factors that mostly influence the quality of our life. As a matter of fact, it is a life-long process, on which we may work up to the last minute. Another important factor is that the process is able to become ‘self-propelled’, meaning that over time the supported person, group, etc. shall learn the philosophy, approach and the know-how of coaching, enabling the independent and successful use of the method and the tools learnt and practised in coaching later. I seek to present all this with particular attention given to presenting the ideology of coaching from several perspectives via the historic milestones, the demonstration of its mechanism, the conclusions to be drawn from the connections and the challenges of the future. A further objective of the present study is to shed light on the potential of coaching to support the operation of the internal control systems of organisations via their managers.